PRESIDENT PRABOWO’S POLITICAL AUTHORITY AT SPIEF 2025: AN INTERPERSONAL MEANING AND SOCIAL EMBODIMENT ANALYSIS - Kusuma Arum Diana Kumara; Galuh Kirana Dwi Areni (English Study Program University of Pasir Pengaraian, 2026)
Political authority is constructed not only through what leaders say but also through how interpersonal meanings are realized in discourse. While previous studies have widely examined political speeches through Systemic Functional Linguistics (SFL), no study has investigated how authority is enacted across different discourse contexts within the same international forum, particularly by non-Western leaders. Using a qualitative descriptive approach, this study investigates the enactment of authority in President Prabowo Subianto’s discourse at the St. Petersburg International Economic Forum (SPIEF) 2025. Drawing on the interpersonal metafunction of SFL, it analyzes Mood Types, Modality, and Polarity in a speech and a panel session. Social embodiment is employed as a supporting perspective to explain how embodied resources contribute to the realization of interpersonal meanings. The findings indicate that authority in both datasets is realized primarily through Declarative–No Modality–Positive Polarity (D–Ø–Ø–P) constructions, which present political propositions as factual, legitimate, and undeniable. Obligation, negative Polarity, and limited imperative patterns further reinforce authority through commitment, rejection, and persuasive direction. The findings also reveal contextual variation: authority in the speech is more assertive and policy-oriented, whereas authority in the panel session is more negotiated and diplomatically moderated. Embodied resources support these meanings by reinforcing certainty and commitment or by softening directive force. The study concludes that political authority is dynamically constructed through the interaction of interpersonal grammatical resources and embodied support in contemporary political discourse.